FOLFOX+Nab-Paclitaxel (FOLFOX-A) for Advanced Pancreatic Cancer: A Brown University Oncology Research Group Phase I Study. (December 2016) - Safran, Howard; Charpentier, Kevin P.; Perez, Kimberly; Mantripragada, Kalyan; Miner, Thomas; DiPetrillo, Thomas; Kuritzky, Benjamin; Apor, Emmanuel; Bishop, Kenneth; Luppe, Denise; Mitchell, Kristen; Rosati, Kayla
Abstract : Background: The Brown University Oncology Research Group performed a phase I study to remove irinotecan from FOLFIRINOX (5-fluorouracil, oxaliplatin, irinotecan, and leucovorin) and substitute nab-paclitaxel. Methods: Patients with newly diagnosed advanced pancreatic adenocarcinoma were eligible. Patients received oxaliplatin 85 mg/m 2, leucovorin 400 mg/m 2, and 5-fluorouracil 2400 mg/m 2 with 3 dose levels of nab-paclitaxel (125, 150, and 175 mg/m 2 ) every 2 weeks. Dose-limiting toxicities were assessed in the first 2 cycles of treatment. The final dose level was expanded to assess cumulative neurotoxicity. Results: Thirty-five patients were entered; 24 with metastatic and 11 with locally advanced pancreatic cancer. The maximum tolerated dose of nab-paclitaxel was 150 mg/m 2 every 2 weeks with FOLFOX. Cumulative neuropathy was the most important toxicity. Grade 3 neuropathy developed in 2 of the first 6 patients at 10 and 11 cycles of FOLFOX-A. Following an amendment to reduce oxaliplatin to 65 mg/m 2 if grade 2 neuropathy developed, no additional patients developed grade 3 neurotoxicity. Twenty-one of 35 patients (60%) had a partial response. The median survival for patients with metastatic disease was 15 months. Conclusions: The maximum tolerated dose of nab-paclitaxel is 150 mg/m 2 every 2 weeks with FOLFOX. The regimen of FOLFOX-A represents a promising treatment for pancreatic cancer.